MODEL PEMBELAJARAN ATLETIK NOMOR LEMPAR LEMBING UNTUK ANAK TUNAGRAHITA RINGAN - Luthfe Lufthansa (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2016)
AbstractThis study aims to develop a learning model of javelin games in athletics for slightly mentally retarded children. Theresearch and development study was conducted in the research and development steps as follows: (1) collectinginformation in the feld, (2) analyzing the information, (3) developing the preliminary product, (4) conducting expertvalidation and revision, (5) conducting a small-group feld tryout and revision, (6) conducting a large-group feld tryoutand revision, and (7) making the fnal product. The data collection instruments included: (1) an interview guideline,(2) a grade scale, and (3) an observation guideline. The data were analyzed by means of quantitative and qualitativedescriptive techniques. The study produces a guidebook for the learning of throwing games in athletics for slightlymentally retarded children consisting of eight models, i.e.: (1) a learning model of the tabok ball netting,(2) a learning model of the throw, (3) a learning model of throwing a tailed ball at a hanging hoop target, (4) a learningmodel of throwing a rocket to a star.Keywords: Slightly Mentally Retarded Children, Athletics Learning, DevelopmentAbstrakPenelitian ini bertujuan menghasilkan model pembelajaran atletik nomor lempar lembing untuk anak tunagrahitaringan. Penelitian dan pengembangan ini dilakukan dengan langkah- langkah sebagai berikut: (1) pengumpulaninformasi di lapangan, (2) analisis terhadap informasi, (3) pengembangan produk awal, (4) validasi ahli dan revisi,(5) uji coba lapangan kelompok kecil dan revisi, (6) uji coba lapangan kelompok besar dan revisi, dan (7) pembuatanproduk fnal.Instrumen pengumpulan data yang digunakan yaitu: (1) pedoman wawancara, (2) skala nilai, dan (3)pedoman observasi. Teknik analisis data yang dilakukan yaitu teknik analisis deskriptif kuantitatif dan analisis deskriptifkualitatif. Penelitian menghasilkan buku panduan pembelajaran atletik nomor lempar untuk anak tunagrahita ringanyang berisikan empat model, yaitu (1) model pembelajaran bermain netting tabok bola, (2), model pembelajaranmelempar, (3) model pembelajaran melempar bola berekor dengan sasaran simpai yang digantung, (4) modelpembelajaran melempar roket ke bintang.Kata Kunci: Anak Tunagrahita Ringan, Pembelajaran Atletik, Pengembangan